Autochthonous Blastomyces dermatitidis, India - Anuradha Chowdhary; Gaston I. Jofre; Ashutosh Singh; Andrius J. Dagilis; Victoria E. Sepúlveda; Allison T McClure; Daniel R. Matute (Emerging Infectious Diseases, 2024)
Blastomyces spp. fungi, the causal agent of blastomycosis, are common in North America but do occur in other areas of the world. The most prevalent pathogen in the genus is B. dermatitidis. Most B. dermatitidis isolates originate from North America, but there are sporadic reports of B. dermatitidis recovery from Africa and Asia. High-quality reports that incorporate genetic information about the fungus outside North America have been rare. Genome sequencing of 3 fungal isolates from patients in India with chronic respiratory diseases revealed that the isolates belong to a genetically differentiated lineage of B. dermatitidis. Because the patients had no history of traveling outside of Asia, blastomycosis was most likely autochthonously acquired, which suggests a local population of B. dermatitidis. Our results suggest the endemic range of B. dermatitidis is larger than previously thought, calling for a reassessment of the geographic range of different agents of endemic mycoses.